EKPLORASI BAKTERI SELULOLITIK DARI CAIRAN RUMEN SAPI PERANAKAN FRIES HOLLAND (PFH) DAN LIMOUSINE PERANAKAN ONGOLE (LIMPO) - Sekar Ayu Yogyaswari; MG. Isworo Rukmi; Budi Raharjo (Jurnal Akademika Biologi, 2016)
Cellulose is the largest component of plant materials which is the most abundant organic compound in nature. The degradation of cellulose carried out by cellulase enzymes which is consisting of three components, i.e. , endoglucanase, exoglucanase, and β-glucosidase with glucose as the end product. Cellulase is very useful in industry and agriculture, such as paper, beer and brewing industries, for improving the quality of forages, organic material decomposer, and play an important role in the bioconversion of cellulose into various chemical commodities. The aims of this study was to get cellulolytic bacteria from cow’s rumen fluid which has high cellulolytic activity. Isolation of cellulolytic bacteria from cow’s rumen fluid were done by direct plating on CMC media. The cellulolytic activity values of the bacterial isolates were examined by determining cellulolytic index. The determination of cellulase activity were carried out by DNS method while the total protein contents by Lowry method. Identification of the bacteria isolates were done by observation of colony morphology, microscopic observation, and biochemical tests. Six potential cellulolytic bacterias were obtained in this study and all isolates identified as Bacillus. The highest cellulase specific activity shown by Fh-9 and Lo-8 isolates in 8 hours incubation.Keywords: cellulolytic bacteria, cellulose, cellulase.